Overview of Methods for Noise and Heat Reduction in MRI Gradient Coils - Motovilova, Elizaveta; Winkler, Simone Angela (Frontiers in Physics, 2022)
MRI gradient coils produce acoustic noise due to the coil conductor vibrations caused by large Lorentz forces. Accurate sound pressure levels and modeling of heating are essential for the assessment of gradient coil safety. This work reviews the state-of-the-art numerical methods used for accurate gradient coil modeling and prediction of sound pressure levels (SPLs) and temperature rise. We review several approaches proposed for noise level reduction of high-performance gradient coils with a maximum noise reduction of 20 dB demonstrated. An efficient gradient cooling technique is also presented.